The socioeconomic factors affecting families' secondary school choice for their children among selected barangays in Miag-ao - Javellana, Carl Mark
The research study determines the significant socioeconomic factors that influence families'secondary school choice for their children, and also ascertains how these significant socioeconomic predictors affect school choice.